2020
DOI: 10.1038/s41598-020-72319-6
|View full text |Cite
|
Sign up to set email alerts
|

Green tea consumption increases sperm concentration and viability in male rats and is safe for reproductive, liver and kidney health

Abstract: Green tea is a popularly consumed beverage worldwide and contains polyphenols, whose antioxidant activities could improve sperm parameters and fertility thereof. We investigated the effect of green tea on the male rat reproductive system as well as its safety. Male Wistar rats were administered 2 and 5% aqueous extract of green tea for 52 days’ ad libitum, while the control group received tap water. Total polyphenol, flavanol, flavonol and soluble solids significantly increased in a concentration-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 93 publications
(141 reference statements)
0
24
1
Order By: Relevance
“…Consistently, the ad libitum administration of 2% and 5% aqueous extract of green tea for 52 days increased sperm concentration and viability in rats, [ 136 ]. In the same study, the authors revealed spontaneous acrosome reaction and morphological changes in testis and epidydimis, with increased cauda epididymis epithelial height and decreased diameter and epithelial height of seminiferous tubules [ 136 ]. Similar effects on sperm vitality, motility, acrosome reaction, and morphological parameters in the seminiferous tubules and epididymis were observed following black tea administration [ 137 ].…”
Section: Action Of Polyphenols On Some Hallmarks Of Agingmentioning
confidence: 86%
See 1 more Smart Citation
“…Consistently, the ad libitum administration of 2% and 5% aqueous extract of green tea for 52 days increased sperm concentration and viability in rats, [ 136 ]. In the same study, the authors revealed spontaneous acrosome reaction and morphological changes in testis and epidydimis, with increased cauda epididymis epithelial height and decreased diameter and epithelial height of seminiferous tubules [ 136 ]. Similar effects on sperm vitality, motility, acrosome reaction, and morphological parameters in the seminiferous tubules and epididymis were observed following black tea administration [ 137 ].…”
Section: Action Of Polyphenols On Some Hallmarks Of Agingmentioning
confidence: 86%
“…For example, tea polyphenols, known as catechins, decreased the apoptosis rate of spermatogenic cells in rats with experimental varicocele [135]. Consistently, the ad libitum administration of 2% and 5% aqueous extract of green tea for 52 days increased sperm concentration and viability in rats, [136]. In the same study, the authors revealed spontaneous acrosome reaction and morphological changes in testis and epidydimis, with increased cauda epididymis epithelial height and decreased diameter and epithelial height of seminiferous tubules [136].…”
Section: Polyphenols and Male Fertilitymentioning
confidence: 97%
“…However, a significant increase in spontaneous acrosome reactions was observed. Finally, the antioxidant defenses (CAT, GSH, MDA, and SOD levels) remain unchanged, indicating the safety of green tea consumption and a balance of the oxidative stress status of the tissues [158].…”
Section: Green Teamentioning
confidence: 99%
“…On the other hand, a certain physiological amount of ROS activity is essential for spermatogenesis and normal sperm functions. Thus, excessive use of antioxidants can have a negative effect on spermatogenesis and male fertility [65,66]. This might be the reason as to why Aboua et al [67] noted a significant decline in the motility of spermatozoa in vitro after exposure to RPO.…”
Section: Red Palm Oil In Male Infertility Preventionmentioning
confidence: 99%